ANALISIS PENGARUH GREEN ACCOUNTING DAN KUALITAS AUDIT TERHADAP NILAI PERUSAHAAN (Sektor Properti, Real Estate dan Konstruksi Bangunan yang Terdaftar di BEI Tahun 2017-2021) - Mutia Faranika; Ilham Illahi (Jurnal Ekonomi dan Bisnis, 2023)
This research constitutes a quantitative investigation designed to explore and assess the influence of green accounting and the quality of audits on the valuation of companies operating within the property, real estate, and building construction sectors, which are listed on the Indonesia Stock Exchange (IDX) over the timeframe spanning 2017 to 2021. A total of 37 enterprises were selected as representatives via the purposive sampling technique. The dataset employed in this research is of a secondary nature and was sourced from the IDX's official website as well as the individual companies' respective websites. The process of data analysis was conducted utilizing the methodology of multiple linear regression, while the verification of hypotheses was carried out through the utilization of SPSS version 26 software. The findings stemming from the initial hypothesis demonstrate that sustainable accounting exerts a discernible impact on the valuation of firms, evidenced by a significance value of 0.002, a figure lower than the established threshold of 0.05. In line with the second hypothesis, it is evidenced that the quality of audits also bears influence on the valuation of firms, with a significance value of 0.009, similarly falling beneath the 0.05 threshold. On a different note, the third hypothesis indicates that the combined effect of sustainable accounting and audit quality holds sway over firm valuation, marked by a significance value of 0.002. In light of the coefficient of determination (R2) assessment, a value of 0.106 has been ascertained. This signifies that the cumulative contribution of sustainable accounting and audit quality amounts to 10.6% of the variation observed in firm valuation across the property, real estate, and building construction sectors on the IDX. The remaining 89.4% is subject to the influence of other factors that remain unexplored within the scope of this study.